PENERAPAN PRINSIP-PRINSIP INTERNATIONAL CONVENTION ON TRAVEL CONTRACTS DALAM TRANSAKSI JASA PERJALANAN WISATA - Irma Prawita Saragih; Ida Bagus Wyasa Putra; Made Suksma Prijandhini Devi Salain (Kertha Negara : Journal Ilmu Hukum, 2014)
The legal relationship between the travel agency with consumer services travel services (travel) between the members agent or travel services (travel) is subject to the provisions of contract law in Indonesia and in particular, it is also regulated under the International Convention Travel Contract. In fact, not all travel service agency contracts in Denpasar-Bali refer to the provisions of the convention in concern. It shows that the contract lacked thecapacity to prevent disputes, control of potential disputes, and resolve issues arising from a contract that has been made.